Tubo-Ovarian Transitional Cell Carcinoma and High-grade Serous Carcinoma Show Subtly Different Immunohistochemistry Profiles. (November 2019) - Magrill, Jamie; Karnezis, Anthony N.; Tessier-Cloutier, Basile; Talhouk, Aline; Kommoss, Stefan; Cochrane, Dawn; Chow, Christine; Cheng, Angela; Soslow, Robert; Hauptmann, Steffen; du Bois, Andreas; Pfisterer, Jacobus; et al.
Abstract : Tubo-ovarian transitional cell carcinoma (TCC) is grouped with high-grade serous carcinoma (HGSC) in the current World Health Organization classification. TCC is associated with BRCA mutations and a better prognosis compared with HGSC. Previous papers examining the immunohistochemical features of TCC have studied limited numbers of samples. No marker reflecting the biological difference between TCC and HGSC is known. We collected a large cohort of TCC to determine whether TCC and HGSC could be distinguished by immunohistochemistry. A tissue microarray was built from 89 TCC and a control cohort of 232 conventional HGSC. Immunohistochemistry was performed, scored, and statistically analyzed for routine markers of HGSC and urothelial tumors: PAX8, WT1, p53, p16, ER, p63, and GATA3. Using scoring cutoffs commonly employed in clinical practice, the immunohistochemical profile of TCC was indistinguishable from HGSC for all markers. However, more detailed scoring criteria revealed statistically significant differences between the 2 groups of tumors with respect to ER, PAX8, and WT1. HGSC showed more diffuse and intense staining for PAX8 ( P =0.004 and 0.001, respectively) and WT1 ( P =0.002 and 0.002, respectively); conversely, TCC showed more intense staining for ER ( P =0.007). TCC and HGSC therefore show subtle differences in their immunohistochemical profiles which might reflect underlying (epi)genetic differences. Further studies using proteomic analysis will focus on the identification of differentially expressed proteins that might serve as markers of TCC-like differentiation, which could help explain biologic differences between TCC and HGSC and might identify other cases of HGSC with a better prognosis.